GRAMMARS AND BRAZILIAN PORTUGUESE LANGUAGE TEACHING: COMPARATIVE ANALYSIS OF PERSONAL PRONOUNS WORD CLASS (Muitas Vozes, 2021)
In this paper, we cover three stages of Grammars in Brazilian Portuguese Language teaching. In order to demonstrate how different materials operate, we perform a comparative analysis of the class “personal pronouns” in a Traditional Grammar, a Textbook and a Scientific Grammar. We associate this analysis to the presentation of the following contexts: the establishment of Brazilian Grammatical Nomenclature (NGB), the proposition of the Textbook National Program (PNLD) and the production of grammars by linguists. The data discussion showed that, from the point of view of definitions, there is a consonance between Traditional Grammar and the Textbook, both guided by the NGB. In Scientific Grammar, on its turn, different types of pronouns are grouped and presented as members of different processes that occur in the language. From the point of view of functions, the Textbook, as well as the Scientific Grammar, illustrate the importance of the context for understanding the functioning of the word class under analysis. In its turn, Traditional Grammar demonstrates its prescriptive character, because, in addition to being primarily based on decontextualized literary examples, it presents uses of pronouns that are considered “wrong”. In conclusion, we highlight that there is no definitive grammatical method or manual for Brazilian Portuguese Language teaching, but rather works that complement each other and can be used together for this purpose.